2018
DOI: 10.1111/acem.13651
|View full text |Cite
|
Sign up to set email alerts
|

“Full Stomach” Despite the Wait: Point‐of‐care Gastric Ultrasound at the Time of Procedural Sedation in the Pediatric Emergency Department

Abstract: Objectives:The objective was to use gastric point-of-care ultrasound (POCUS) to assess gastric contents and volume, summarize the prevalence of "full stomach," and explore the relationship between fasting time and gastric contents at the time of procedural sedation.Methods: This was a prospective study of patients aged 2 to 17 years fasting prior to procedural sedation. A single sonographer scanned each patient's gastric antrum in two positions: supine with the upper body elevated and right lateral decubitus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 30 publications
3
35
0
1
Order By: Relevance
“…In our cohort of children with acute appendicitis, gastric contents were not associated with the duration of fasting or abdominal pain. Recent ultrasound studies have likewise reported a poor correlation between gastric contents and fasting time in acutely ill children, both in the emergency department [21][22][23] and in the operating theatre [9].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort of children with acute appendicitis, gastric contents were not associated with the duration of fasting or abdominal pain. Recent ultrasound studies have likewise reported a poor correlation between gastric contents and fasting time in acutely ill children, both in the emergency department [21][22][23] and in the operating theatre [9].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 82% of patients showed an empty stomach after a median NPO time of 7.5 hours for solid intake and 6 hours for clear liquid intake. This study included a population with lower age group, weight, and height but similar body mass index than in other studies [20][21][22]34]. The ROC analysis suggested the optimal cut-off of solid food NPO duration for gastric emptying was 6.5 hours when the patients had more than 2 hours of liquid fasting.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated the prevalence of an empty stomach on gastric POCUS in pediatric patients requiring PSA in the PED. Leviter et al [21] reported that only 31% of patients had an empty stomach after 5.8 (4.6-7.7) hours of solid fasting and 5.2 (4.1-6.8) hours after liquid fasting. Moake et al [22] conducted a study on 93 patients with PSA, and reported that gastric emptying could be confirmed in only 20% of patients fasting more than 6 hours and in less than 40% of patients fasting for more than 8 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Šiuo metu trūksta daugiau tyrimų ir naujesnių duomenų apie skrandžio turinio įvertinimą vaikų populiacijoje, todėl negalime teigti, jog vienas ar kitas metodas yra pranašesnis. Remiantis literatūra, badavimas, trunkantis 6 ar daugiau valandų, neužtikrina tuščio skrandžio vaikų populiacijoje [56], todėl siekiant išvengti su aspiracija susijusių komplikacijų, turėtų būti svarstoma skrandžio turinio įvertinimo UG galimybė.…”
Section: Tiriamųjų Amžiusunclassified